MULTILINGUISTICISM IN THE LINGUISTIC LANDSCAPE OF TRANSPORTATION IN KUPANG - Norci Beeh; Seprianus Arwadi Nenotek; Alfred Snae; Naniana Nimrot Benu (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
This article discusses the language form and the symbolic function of quotes or slogans on transportation around Kupang city. The data of this study were collected directly from the transportation around the streets. They were analyzed using qualitative methods, while the symbolic functions were analyzed using a critical discourse analysis model. It found that land transportation uses multi-languages, English, Indonesian, Kupang Malay, Uab Meto (Dawan), Rote, Sabu, Hebrew, Latin, and Betawi. Some use a particular style of language, such as p27den, and a combination of two or more languages or dialects. English is the most dominant language used. The lack of local languages shows massive cultural changes and people's attitudes toward local languages. The linguistic unit consists of words, phrases, clauses, sentences, and acronyms. English is dominant in each linguistic unit except in acronyms. The quotes represent six themes: love, religion, music, power, family, and regionalism. In general, They carry two functions, power relations, and identity.